Simultaneous estimation of bisoprolol fumarate and cilnidipine in tablet dosage form using rp-hplc method - REVATHY A KUMAR; ASHA THOMAS (International Journal of Pharma and Bio Sciences, 2018)
A simple and precise Reverse-phase high performance liquid chromatography method has been developed and validated for simultaneous estimation of Bisoprolol fumarate (BISO) and Cilnidipine (CIL) in tablet dosage forms. The separation was achieved on a Agilent Eclipse plus C18 (4.6 x 100 mm) 3.5µm column with isocratic flow. The mobile phase was Water (pH 5.6): Methanol (20:80) at a flow rate of 1 ml/mint. The UV detection was carried out at 232 nm. The BISO and CIL were separated with good resolution at Rt 1.50 and 1.31 respectively, without interference of excipients. A linear response was observed over a concentration range of 5-25 µg/ml for both BISO and CIL. The LOD and LOQ values for BISO were 0.003 µg/ml and 0.0091µg/ml respectively and for CIL were 0.159µg/ml and 0.48µg/ml respectively. The method was validated according to ICH guidelines acceptance criteria for linearity, accuracy and precision. The proposed method can be used in quality control analysis of pharmaceutical dosage forms containing Bisoprolol fumarate and Cilnidipine.